The systematics and ecological role of Histioteuthis (Cephalopoda: Histioteuthidae) in New Zealand waters - Horstkotte, Jens (2008)
Several recent publications revised the family Histioteuthidae, but their distribution and diversity in New Zealand waters remains unclear. Herein, hitherto unreported collections are examined to define the number of species found in these waters. Each species is described in detail and its distribution is discussed. Histioteuthids play a major role for marine apex predators as sperm whales (Physeter macrocephalus), pygmy sperm whales (Kogia breviceps), fishes and albatrosses. Their indigestible beaks can occur in hundreds to thousands in stomachs of predators, and often are used to reconstruct the diets of these predators. Herein, new species-specific equations for estimating mantle length and weight by measuring the lower rostral length are calculated for three species, and for the first time equations for Histioteuthis corona cerasina are calculated. Morphology of the upper beak is described and equations for 4 species are calculated to estimate mantle length and weight by measuring 2 different characters of the upper beak. The ecological role of each species occurring in New Zealand waters is defined, based on data from literature and the distribution of the species. Histioteuthis atlantica appears to be the most abundant species, followed by H. macrohista and H. miranda. As indicated by the abundance, H. atlantica is the most important histioteuthid species for sperm whales; for pygmy sperm whales, H. miranda is the most important prey species. Histioteuthis macrohista, due to it relatively small size, is not of crucial importance for predators in New Zealand waters. The unidentified species Histioteuthis type AS is believed to not occur in New Zealand waters, but one beak of this species was found in the stomachs of pygmy sperm whales, that mainly feed on locally occurring squid species. This indicates that Histioteuthis type AS either does occur in New Zealand waters or that the pygmy sperm whale also feeds outside these waters.